Le faune et la sirène : la situation de Cuvier dans l’économie de The Marble Faun, de Nathaniel Hawthorne - Antoine Traisnel (Transatlantica)
Nathaniel Hawthorne’s The Marble Faun ends with one character’s polite refusal to satisfy the narrator’s curiosity concerning young Donatello’s possible animality. When asked if Donatello’s ears are as pointy as those of the book’s titular figure, the Faun of Praxiteles, Kenyon smiles inscrutably and responds: “On that point, at all events, there shall be no word of explanation.” On that “point” – that of Donatello’s ears—the author remains obstinately tight-lipped, having “hoped to mystify this anomalous creature between the Real and the Fantastic […] without impelling him to ask how Cuvier would have classified poor Donatello.” The disclosure of a small anatomical detail threatens to shatter the whole edifice of Hawthorne’s fiction. The point in question here, however, is not just the extremity that makes measurement possible but also the ungraspable limit (the punctum) that undoes the logic of Cuvierian classification. Analyzing the metrics of The Marble Faun, my paper will query how the romance envisions the vanishing point of the human/animal relation.